2021
DOI: 10.3390/cancers13112514
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Gut Microbiota: An Emerging Source of Biomarkers for Immune Checkpoint Blockade Therapy in Non-Small Cell Lung Cancer

Abstract: Background: The human gut harbors around 1013–1014 microorganisms, collectively referred to as gut microbiota. Recent studies have found that the gut microbiota may have an impact on the interaction between immune regulation and anti-cancer immunotherapies. Methods: In order to characterize the diversity and composition of commensal microbiota and its relationship with response to immune checkpoint blockade (ICB), 16S ribosomal DNA (rDNA) sequencing was performed on 69 stool samples from advanced non-small cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 69 publications
0
15
2
Order By: Relevance
“…Recent studies have demonstrated that gut microbiome is associated with NSCLC progression. Patients with higher gut microbiota alpha diversity ( Zhang C. et al., 2021 ), and those enriched in some microbes, such as Phascolarctobacterium ( Zhang F. et al., 2021 ), Ruminococcaceae UCG 13 , and Agathobacter ( Hakozaki et al., 2020 ), were found to have better PFS. In the current study, we found that the long-PFS group had the highest F/B value and significantly higher diversity in Fungi, Archaea, and Viruses among three groups.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that gut microbiome is associated with NSCLC progression. Patients with higher gut microbiota alpha diversity ( Zhang C. et al., 2021 ), and those enriched in some microbes, such as Phascolarctobacterium ( Zhang F. et al., 2021 ), Ruminococcaceae UCG 13 , and Agathobacter ( Hakozaki et al., 2020 ), were found to have better PFS. In the current study, we found that the long-PFS group had the highest F/B value and significantly higher diversity in Fungi, Archaea, and Viruses among three groups.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroides vulgatus has been associated with the reduced risk of immune-related adverse events ( Usyk et al, 2021 ), including dermatological skin toxicity (where B. dorei anti-correlated) ( Zhang et al, 2021 ). Furthermore, B. vulgatus has been shown to be protective against Escherichia coli induced colitis of interleukin-2-deficient gnotobiotic mice ( Waidmann et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, the researchers were able to demonstrate in this study that the response effect could be transferred to mice with a poor response via a fecal microbiome transplant. Furthermore, B. vulgatus was also increased in non-small cell lung cancer patients that did not experience dermatological irAE, following PD1-based ICB treatment [ 42 ].…”
Section: Discussionmentioning
confidence: 99%